Pengembangan Media Komik Digital Untuk Meningkatkan Kemampuan Berbahasa Anak Usia 5-6 Tahun - Naura Nazifa R. Hidayat; Irmawati; Nurul Amaliah Hasbi; Nurul Fatiha Arifin (Al-Mudarris, 2026)
The limited language skills of early childhood learners and the lack of diverse instructional media highlight the need for technologically enhanced innovations with meaningful pedagogical value. This study aimed to develop an interactive digital comic based on Islamic values to enhance the language skills of children aged 5–6 years through a digital storytelling and multimodal literacy approach. The study employed the Four-D (4-D) development model, consisting of the Define, Design, Develop, and Disseminate stages. The participants included 14 Group B kindergarten children and five teachers at TK Muttiama Kasih, Majene Regency, Indonesia. Data were collected through structured observations, expert validation sheets, teacher response questionnaires, and language skills assessments. The expert validation results yielded a mean score of 3.65, indicating that the media was highly valid. The practicality test achieved a score of 98.07%, categorized as highly practical. The effectiveness test demonstrated substantial improvements across all language skill indicators, with the average achievement increasing from 22.2% to 87.5%, while the highest achievement reached 100% in the phonemic literacy indicator. Teacher responses reached 100%, indicating that the media was highly effective. The developed media integrates learner-centered interactive visual storytelling with the internalization of the Islamic value of taʿāwun (mutual assistance) through narrative-based modeling, simultaneously fostering children's receptive, expressive, and emergent literacy skills while promoting Islamic character development. Therefore, the interactive digital comic is a feasible and innovative instructional medium that can serve as an effective instrument of tarbiyah in early childhood education.